An Analysis of Linguistic Politeness’ Strategies in a Superior / Subordinate Communication: A Speech Event in a University Setting - Amadi, Scholastica C.; Maduako, Ibiere Ken - (NIU Journal of Humanities, 2019)
The multitude of linguistic strategies that characterize superior/subordinate communications can be gleaned from face-to-face interactions, letters, circulars, memos, notices and so on. Drawing upon the sociolinguistic theory of politeness, this paper described the linguistic politeness strategies used in superior/subordinate communication in a university in terms of exercising power and resolving conflicts. Data analysed in this paper were drawn from face-to-face interactions at a departmental meeting between Head of Department and lecturers. The findings showed that while the superiors’ politeness strategies comprise a mixture of imperatives, interrogatives and declaratives the subordinates used mainly impressive declaratives and interrogatives to demonstrate regard and circumspection. The paper concluded that the bidirectional nature of power in superior-sub-ordinate communications determines politeness tactics. The choice of linguistic forms used in exercising these roles would help regulate human conduct, reduce and eliminate forms of misconduct that breeds conflict, especially if superiors’ and even subordinates’ power and face are diminished, ignored or blurred through wrong choice of linguistic strategies. Keywords: language, politeness strategies, superior-subordinate communication, politeness